2012
DOI: 10.1590/s0100-879x2012007500062
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of circulating peptide YY and ghrelin with body weight, rate of weight gain, and time required to achieve the recommended daily intake in preterm infants

Abstract: The objective was to elucidate the relationships between serum concentrations of the gut hormone peptide YY (PYY) and ghrelin and growth development in infants for potential application to the clinical observation index. Serum concentrations of PYY and ghrelin were measured using radioimmunoassay from samples collected at the clinic. For each patient, gestational age, birth weight, time required to return to birth weight, rate of weight gain, time required to achieve recommended daily intake (RDI) standards, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In the present study a significant positive correlation was observed between plasma PYY levels and energy intake in infants. These data partially confirm the observations of Chen et al [44] that PYY plasma concentrations correlate with a negative energy balance. The other explanation for reduced PYY concentrations in children fed parenterally is the typical action of PYY.…”
Section: Correlationssupporting
confidence: 91%
“…In the present study a significant positive correlation was observed between plasma PYY levels and energy intake in infants. These data partially confirm the observations of Chen et al [44] that PYY plasma concentrations correlate with a negative energy balance. The other explanation for reduced PYY concentrations in children fed parenterally is the typical action of PYY.…”
Section: Correlationssupporting
confidence: 91%
“…Six articles met the criteria for meta-analysis (19,20,(23)(24)(25)(26). The excluded articles from the study (n=23) included the following: 5 articles presented the effect of breast milk ghrelin on growth in infants (6,18,21,22,27), 8 articles expressed no correlation between infants' serum ghrelin and growth (2, 17, 28-33), 3 articles were of descriptive nature (34-36), and 6 articles had an intervention group (37)(38)(39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%
“…Neuropeptide Y (NPY), the most potent brain orexigenic peptide, increases body weight and adiposity [ 18 ]. Conversely, peptide YY inhibits food intake and weight gain and opposes the effects of ghrelin on food intake and energy balance [ 19 , 20 ]. The incretin hormones, glucagon-like peptide-1 (GLP-1) and insulin-like growth factors 1 and 2 (IGF-1 and -2), generally have anorectic properties [ 15 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%